Pengaruh Pendampingan Orang Tua dalam Belajar terhadap Kemampuan Anak Mengenali Diri di Masa Pandemi COVID-19 - Dwiyanti Setyaningsih; Mas’udah Mas’udah (PRESCHOOL: Jurnal Pendidikan Anak Usia Dini, 2021)
This research is motivated by the assistance of parents in learning activities from home which is not optimal because both parents work, so that the ability to know themselves in children is not stimulated properly. This study aims to determine the effect of parental assistance in learning activities from home on the ability to recognize self in early childhood. This study uses a quantitative approach with a survey research design. The sampling technique was total sampling, ie the entire population in TK Kurnia Surabaya was used as a sample. The sample of this study consisted of 36 guardians of Kurnia Kindergarten Surabaya students. The data collection technique in this study was using a questionnaire or questionnaire. Based on the results of the t-test on the SPSS application, it explains that the significance value (Sig) is 0.035 <0.05, which means Ha is accepted and H0 is rejected so that Parental Assistance (X) affects the Ability to Know Yourself in Children (Y). The result of the calculation of the Coefficient of Determination (R2) on SPSS is 0.124 or the equivalent of 12.4%. so that it can be concluded that the ability to know oneself in children 12.4% is influenced by Parental Assistance, the rest is influenced by other variables that are not known by the researcher. Penelitian  ini dilatarbelakangi oleh pendampingan orang tua dalam kegiatan belajar dari rumah yang tidak maksimal karena kedua orang tua bekerja, sehingga kemampuan mengenal diri pada anak tidak terstimulasi dengan baik. Penelitian ini bertujuan  untuk  mengetahui  pengaruh  pendampingan orang tua dalam kegiatan belajar dari rumah terhadap kemampuan mengenal diri anak usia dini. Penelitian  ini menggunakan pendekatan kuantitatif dengan desain penelitian survei. Teknik  sampling  dilakukan  secara total  sampling,  yakni  seluruh  populasi  di  TK Kurnia Surabaya dijadikan sebagai  sampel.  Sampel penelitian ini  terdiri atas  36  wali murid TK Kurnia Surabaya. Teknik pengumpulan data dalam penelitian ini adalah menggunakan angket atau kuisoner. Berdasarkan hasil uji t pada aplikasi SPSS memaparkan bahwa nilai signifikansi (Sig) 0.035 < 0.05 yang artinya Ha diterima dan H0 ditolak sehingga pendampingan orang tua (X) berpengaruh pada kemampuan mengenal diri pada anak (Y).  Hasil perhitungan koefisien determinasi (R2) pada SPSS ialah 0.124 atau setara 12.4%. sehingga dapat ditarik kesimpulan bahwa kemampuan mengenal diri pada anak 12.4% dipengaruhi oleh pendampingan orangt sisanya dipengaruhi oleh variable lainnya yang tidak diketahui oleh peneliti.